Exploatation corpses of prisoners to research by third Reich anatomical institutes - Meler, Jan (Studia Iuridica Toruniensia, 2014)
The article describes the process of using prisoners’ bodies for research by scientist of Third Reich. Anatomical institutes which before the Second World War trained medical students on the basis of few human preparation, between 1939–1945 gained unlimited access to resources of human bodies. The primary source of preparations were prisoners’ decapitated bodies. For the purposes of the national economy Third Reich all corps were deprived of a legal protection. At the same time the Ministry of Justice of Third Reich adopted a regulation which standardized the equipment of dissectingrooms. This situation had given a chance to German scientist to pursue practically all research projects. Some of these project like receiving soap from human fat was the subject of a future investigation conducted by United Nations War Crimes Commission.